2022
DOI: 10.1186/s13089-022-00278-2
|View full text |Cite
|
Sign up to set email alerts
|

Time course of lung ultrasound findings in patients with COVID-19 pneumonia and cardiac dysfunction

Abstract: Background Lung ultrasound (LUS) is a valuable tool to predict and monitor the COVID-19 pneumonia course. However, the influence of cardiac dysfunction (CD) on LUS findings remains to be studied. Our objective was to determine the effect of CD on LUS in hospitalized patients with COVID-19 pneumonia. Material and methods Fifty-one patients with COVID-19 pneumonia participated in the study. Focused echocardiography (FoCUS) was carried out on day 1 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
1
3
0
1
Order By: Relevance
“…The authors found that LV dysfunction was observed in approximately 20% and RV dysfunction in approximately 30% of patients with acute SARS-CoV-2 infection and that age at presentation, previous lung disease, LDH, LVLS, and RVFWS were independently associated with in-hospital mortality. These new findings support the interest in an integrated evaluation of the lungs and cardiac ultrasound function to evaluate the patient’s prognosis, considering that respiratory insufficiency can be a multifactorial decision-making process [ 22 , 23 , 24 ]. However, the routine use of echocardiography among low-risk patients is not recommended.…”
supporting
confidence: 54%
“…The authors found that LV dysfunction was observed in approximately 20% and RV dysfunction in approximately 30% of patients with acute SARS-CoV-2 infection and that age at presentation, previous lung disease, LDH, LVLS, and RVFWS were independently associated with in-hospital mortality. These new findings support the interest in an integrated evaluation of the lungs and cardiac ultrasound function to evaluate the patient’s prognosis, considering that respiratory insufficiency can be a multifactorial decision-making process [ 22 , 23 , 24 ]. However, the routine use of echocardiography among low-risk patients is not recommended.…”
supporting
confidence: 54%
“…Patients with cardiac dysfunction on ultrasound were found to have lower PaO 2 /FiO 2 ratio compared to patients without cardiac dysfunction, leading to higher rates for intubation and ICU admission ( 136 ). In patients with COVID-19 and PE, those with a larger right ventricular diameter on ultrasound required oxygen support more often ( 137 ), and hence may be a potentially useful tool for risk stratification.…”
Section: Discussionmentioning
confidence: 99%
“…Another problem is that the expression of certain diagnostic artifacts of lung and pleural sonography, especially vertical artifacts, depends on the selected transducer (especially central frequency and bandwidth), instrument settings or presets, focus, time-gain compensation (TGC), and the use of artifact minimizing technologies (harmonic imaging, compounding). The available literature is limited and predominantly dates from the last 3 years 23 24 25 26 , which means that the International Consensus Guidelines published in 2012 were not yet able to provide any concrete recommendations 17 . International consensus recommendations from 2023 address the issue in detail and suggest the use of optimized LUS presets, but without detailing specifics 11 .…”
Section: Pleuramentioning
confidence: 99%
“…Presets, der Fokussierung und der Time-Gain-Compensation (TGC) sowie der Verwendung von artefaktminimierenden Technologien (Harmonic Imaging, Compounding) abhängig ist. Die dazu verfügbare Literatur ist begrenzt und stammt vorwiegend aus den letzten 3 Jahren 23 24 25 26 , sodass die 2012 publizierten internationalen Konsens-Guidelines noch keine konkreten Empfehlungen geben konnten 17 . Internationale Konsensempfehlungen aus dem Jahr 2023 gehen zwar detailliert auf das Thema ein und schlagen die Nutzung optimierter LUS-Presets vor, ohne allerdings deren Spezifika detailliert anzugeben 11 .…”
Section: Pleuraunclassified